Dampak Pembelajaran Daring terhadap Minat Belajar Siswa Sekolah Menengah Atas - Desy Sundari; Sukardi Sukardi; Nuranisa Nuranisa (Didaktika : Jurnal Kependidikan, 2021)
Online learning is a decision taken by the government to be able to minimize the transmission of COVID-19, so that the learning process that is usually done directly has to be turned into an online learning process. The problems experienced by students during online learning are, students have difficulty understanding the material provided by the teacher, internet access is not good, assignments from each subject are piled up and students easily feel bored because learning is done online so they have to learn independently at home. at home is different from the learning process that is carried out directly in the classroom. Therefore, every teacher is required to be able to use information technology well so as to be able to provide interesting, creative and maximum learning so that it can attract students' interest in learning. The purpose of this study was to determine the impact of online learning on the interest in learning of class XI students at SMA Negeri 1 Bakam. The method used in this study is a quantitative descriptive method, this study involved 63 students from three classes, namely class XI MIPA, XI IPS 1 and XI IPS 2, with data collection techniques using a questionnaire made in google form as many as fifteen statements. The results of this study indicate that online learning has an unfavorable impact on students' interest in learning, this is evidenced by the percentage value of the student learning interest questionnaire which shows the highest score of 39.7% which is in the poor category. Thus, it can be concluded that online learning has a negative impact on students' interest in learning.Keywords: Online learning, Interest in Learning, Covid-19